The war of the worlds - Sasaki, Chris; Akib, Jamel; Wells, H. G. (Herbert George), 1866-1946. (New York : Sterling Pub., 2007)
An abridged version of H.G. Wells' classic science fiction tale in which, as life on Mars becomes impossible, Martians and their terrifying machines invade the Earth.
4.3
3-6
3-6
Keywords: Human-alien encounters -- Juvenile fiction; Human-alien encounters -- Fiction; Science fiction; Human-alien encounters -- Fiction; Science fiction; Science fiction